2015
DOI: 10.1016/j.ifacol.2015.10.232
|View full text |Cite
|
Sign up to set email alerts
|

Hamiltonian Feedback Design for Mass Action Law Chemical Reaction Networks

Abstract: A special polynomial state feedback structure is proposed for open chemical reaction networks obeying the mass action law (MAL-CRNs) that stabilizes them for any of their admissible positive set of parameters. The proposed feedback makes the closed-loop system a reversible CRN that enables a generalized Hamiltonian description assuming that their number of reversible reactions is less or equal that the number of species. The design is based on solving a mixed integer linear optimization problem (MILP). A simpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…They showed that there are two simple ways to modify the transition from chaotic behaviour, by varying the strength of the feedback and the delay response. Lipták et al [19] considered a general open CSTR system obeying the mass action law. They proposed a class of polynomial feedback that stabilizes the system, which can then be described by a generalized Hamiltonian form.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that there are two simple ways to modify the transition from chaotic behaviour, by varying the strength of the feedback and the delay response. Lipták et al [19] considered a general open CSTR system obeying the mass action law. They proposed a class of polynomial feedback that stabilizes the system, which can then be described by a generalized Hamiltonian form.…”
Section: Introductionmentioning
confidence: 99%